Properties of Crushed Red-Bed Soft Rock Mixtures Used in Subgrade - Huayan Yao; Shanpo Jia; Wenning Gan; Zhenhua Zhang; Kunlin Lu (Advances in Materials Science and Engineering)
Slaking red-bed soft rocks are widely distributed in the south of Anhui Province, China, and several highways will go through this area. It is important to evaluate their physical and mechanical characteristics for the purpose of using this kind of soft rocks as materials for road construction. In this paper, the compacting tests, the resilient modulus tests, the California bearing ratio (CBR) tests, and permeability tests have been carried out on crushed red-bed soft rock mixtures. The test results showed that, for a given degree of compaction, the resilient modulus decreases linearly with the increase of moisture content. For a given moisture content, the resilient modulus and CBR values increase linearly with the increase of compaction degree, while the soaking swelling, water absorption capacity, and permeability coefficient decrease linearly. In other words, the strength and water stability are enhanced with the increase of the degree of compaction. The results demonstrate that the crushed red-bed soft rock mixtures can be directly used as materials for the highway construction by taking corresponding measures.